Revitalizing Village-Owned Enterprises (Bumdes) Through BUMDES Management Training for Sustainable Tourism Development: A Case Study of Rinding Allo Village, Rongkong District - Erwin, Erwin; Rahim, Abd.; Iksan Yusuf, La Ode Muhammad; Dwipatn, I Made Jyotisa Adi; Devi Nugraha, Putu Ananda (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to revitalize BUMDes through BUMDes management training for sustainable tourism development in Rinding Allo Village, Rongkong District. The community service method used is the ABCD method (Asset-Based Community Development). The ABCD method is used to identify the local potential of Rinding Allo village in an effort to improve the management of BUMDes for the development of sustainable tourism. This community service is carried out through four stages, namely: 1) the discovery stage, which identifies positive programs that have been carried out by Rinding Allo village so far and the problems faced related to the management of BUMDes and the development of sustainable tourism. At this stage, it was found that the management of BUMDes in Rinding Allo has not been running optimally due to internal and external problems. 2) the second stage is the dream stage. At this stage the community service team carries out steps and strategies taken in order to achieve the targets and objectives of the community service. At this stage, BUMDes management training will be conducted, providing program recommendations such as providing infrastructure and human resources that support BUMDes management and sustainable tourism development, creating clear regulations related to BUMDes and tourism in Rinding Allo village. 3) the third stage is design. This stage is carried out by designing BUMDes training modules, designing action plans, preparing implementation teams and building collaborative partners. 4) the destiny stage, namely the implementation and sustainability of the program. At this stage the community service team conducts BUMDes management training, mentoring and monitoring BUMDes, network development, promotion and financial management and program evaluation.